Behavioral Response of the Leafcutter Ant, Atta sexdens rubropilosa (Hymenoptera, Formicidae), to Components of Citrus Pulp - Carlos, Amanda A. [UNESP]; Forti, Luiz Carlos [UNESP]; Camargo, Roberto S. [UNESP]; Verza, Sandra S. [UNESP]; Barbosa, Luciano; Lopes, Juliane F. S. [UNESP] (California State University, 2010)
Citrus pulp is an attractive substrate for dicotyledon-cutting ants, due to its physical and chemical properties. In this study, the behavioral response of Atta sexdens rubropilosa workers to different components of the fruit of Citrus sinensis was examined. The removal of these substrates was assessed by visual scanning in the laboratory and in the field. Six behaviors were recorded and the role of the olfactory stimulus in the choice of substrate was examined. Pellets of endocarp were the most collected and processed by workers, and licking the bait was the behavior with the highest average number of workers. The olfactory stimulus was important in the selection of the material, but it alone was not enough to recruit other individuals to the source.
Keywords: Atta; behavior; foraging; olfactory stimulus